Targeting Hypoxia-A2A Adenosinergic Immunosuppression of Antitumor T Cells During Cancer Immunotherapy - Steingold, Joseph M.; Hatfield, Stephen M. (Frontiers in Immunology, 2020)
The blockade of immunological negative regulators offered a novel therapeutic approach that revolutionized the immunotherapy of cancer. Still, a significant portion of patients fail to respond to anti-PD-1/PD-L1 and/or anti-CTLA-4 therapy or experience significant adverse effects. We propose that one of the major reasons that many patients do not respond to this form of therapy is due to the powerful physiological suppression mediated by hypoxia-adenosinergic signaling. Indeed, both inflamed and cancerous tissues are hypoxic and rich in extracellular adenosine, in part due to stabilization of the transcription factor hypoxia-inducible factor 1 alpha (HIF-1α). Adenosine signals through adenosine A2A receptors (A2ARs) to suppress anti-tumor and anti-pathogen immune responses. Several classes of anti-hypoxia-A2AR therapeutics have been offered to refractory cancer patients, with A2AR blockers, inhibitors of adenosine-generating enzymes such as CD39 and CD73, and hypoxia-targeting drugs now reaching the clinical stage. Clinical results have confirmed preclinical observations that blockade of the hypoxia-adenosine-A2AR axis synergizes with inhibitors of immune checkpoints to induce tumor rejection. Thus, A2AR blockers provide a new hope for the majority of patients who are nonresponsive to current immunotherapeutic approaches including checkpoint blockade. Here, we discuss the discoveries that firmly implicated the A2AR as a critical and non-redundant biochemical negative regulator of the immune response and highlight the importance of targeting the hypoxia-adenosine-A2AR axis to manipulate anti-pathogen and anti-tumor immune responses.